69.2k views
5 votes
Help with intergration​

Help with intergration​-example-1

1 Answer

4 votes

Separate the variables.


(dy)/(dx) = x (x - 3) \implies dy = x (x - 3) \, dx

Expand the right side.


dy = (x^2 - 3x) \, dx

Integrate both sides. On the right side, use the power rule on each term.


\displaystyle \int dy = \int (x^2 - 3x) \, dx \implies y = \frac{x^3}3 - \frac{3x^2}2 + C

Given that
y=3 when
x=2, solve for
C.


3 = \frac{2^3}3 - \frac{3\cdot2^2}2 + C \implies C = \frac{19}3

Then the particular solution is


\boxed{y = \frac{x^3}3 - \frac{3x^2}2 + \frac{19}3}

User Pradeep M
by
4.5k points